Mechanical responses of boron-doped monolayer graphene. (June 2019) - Dai, Zhaohe; Wang, Guorui; Zheng, Zhiyue; Wang, Yanlei; Zhang, Shuai; Qi, Xiaoying; Tan, Pingheng; Liu, Luqi; Xu, Zhiping; Li, Qunyang; Cheng, Zhihai; Zhang, Zhong
Abstract: Though pristine graphene exhibits remarkable mechanical and electronic properties, many electromechanical applications may come from chemically doping it with heteroatoms. The goal is to tune the atomic lattice and, in turn, modulate the electronic band structure of graphene – that may also affect the mechanical responses of the graphene sheet. Particularly essential for both practical applications and fundamental interests is to characterize the effect of chemical doping on the mechanical properties of graphene. Here we report graphene can maintain a large fraction of its pristine strength and stiffness after substituting boron for carbon atoms. Counter-intuitively, boron doping can ameliorate the brittle nature of the original lattice by deflecting the cracks and enabling damage-tolerant behaviors. We further offer a direct mapping between the Raman spectra and the measured mechanical performances that can show the relationship between doping structure and mechanical properties of graphene. This work offers important implications for the rational design of graphene-based systems that require chemical modifications and also utilize the mechanics of graphene. Graphical abstract: The effects of boron doping on the mechanical properties and fracture behaviors of graphene are investigated for the first time. Following direct mapping between the Raman parameters and the measured mechanical performance, we clarify the 'chemical substitution and structural vacancy'–'stiffness, failure strength, and damage-tolerant behavior' relation. Image 1